2023
DOI: 10.7554/elife.84387
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation shifts the response of CA1 pyramidal cells to depolarizing ramps via TRPM4 channels with potential implications for place field firing

Abstract: A synergistic combination of in vitro electrophysiology and multicompartmental modeling of rat CA1 pyramidal neurons identified TRPM4 channels as major drivers of cholinergic modulation of the firing rate during a triangular current ramp, which emulates the bump in synaptic input received while traversing the place field. In control, fewer spikes at lower frequencies are elicited on the down-ramp compared to the up-ramp due to long-term inactivation of the NaV channel. The cholinergic agonist carbachol (CCh) r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“… 73 In addition, calmodulin (CAM) binding sites and ATP binding sites were also found at the TRPM4 and TRPM5 channels, and these channels could affect the channel’s Ca2+ sensitivity. 74 …”
Section: Structure and Domain Organization Of The Trpm Channelsmentioning
confidence: 99%
“… 73 In addition, calmodulin (CAM) binding sites and ATP binding sites were also found at the TRPM4 and TRPM5 channels, and these channels could affect the channel’s Ca2+ sensitivity. 74 …”
Section: Structure and Domain Organization Of The Trpm Channelsmentioning
confidence: 99%
“…Another putative substrate for persistent activity relies on the intrinsic bistable dynamic of individual neurons (Zylberberg and Strowbridge 2017). On the single cell level, persistent Na + current (Yamada-Hanff and Bean 2013) in CA1 pyramidal cells, Ca 2+ activated Ca 2+ currents in entorhinal cortical pyramidal cells (Egorov et al 2002) and CA1 pyramidal cells (Combe et al 2023), and low threshold Ca 2+ currents in other cells (Otsuka et al 2001; Perrier et al 2002) have been shown to contribute to regenerative firing, by making the neuron bistable or even multi-stable, and thus more likely to continue firing after excitation is terminated.…”
Section: Introductionmentioning
confidence: 99%
“…Another putative substrate for persistent activity relies on the intrinsic bistable dynamic of individual neurons ( Zylberberg and Strowbridge, 2017 ). On the single-cell level, persistent Na + current ( Yamada-Hanff and Bean, 2013 ) in CA1 pyramidal cells (PYRs), Ca 2+ -activated Ca 2+ currents in entorhinal cortical PYRs ( Egorov et al, 2002 ) and CA1 PYRs ( Combe et al, 2023 ), and L-type Ca 2+ currents in other cells ( Otsuka et al, 2001 ; Perrier et al, 2002 ) have been shown to contribute to regenerative firing, by making the neuron bistable or even multistable, and thus more likely to continue firing after excitation is terminated.…”
Section: Introductionmentioning
confidence: 99%